Entrepreneurial intention of Indian university students: the role of opportunity recognition and entrepreneurship education. Issue 7 (18th August 2020) - Hassan, Aamir; Saleem, Imran; Anwar, Imran; Hussain, Syed Abid
Abstract : Purpose: The purpose of this study is to investigate the impact of opportunity recognition and entrepreneurial self-efficacy on the entrepreneurial intention of Indian university students. This paper also examines the moderating role of entrepreneurship education and gender on the opportunity recognition–intention and self-efficacy–intention relationships. Design/methodology/approach: The data were collected through a comprehensive questionnaire from 334 students having business and management background. Confirmatory factor analysis was used to ensure the reliability and validity of all the constructs, and structural equation modeling was used to test the proposed hypotheses. Findings: This study unveils three important findings. First, opportunity recognition and self-efficacy both show a significant positive impact on the entrepreneurial intention of students. Second, education positively moderates "self-efficacy–intention relationship", and third, gender negatively moderates "opportunity recognition–intention" and "self-efficacy–intention" relationships. Research limitations/implications: This study has been carried out using a sample of students from only one university, and the study included only business and management background students. Similar studies can be conducted by adding more motivational and contextual factors with an increased sample size of students having different educational backgrounds. Practical implications: This study provides pragmatic support to formulate new educational initiatives that can support students in their present or future entrepreneurial projects. Originality/value: This study adds to the scarce literature on opportunity recognition and entrepreneurial intention and also highlights the moderating role of entrepreneurship education and gender on opportunity recognition–intention and entrepreneurial self-efficacy–intention relationships.